PENGARUH PENGANGGARAN PARTISIPATIF, LOCUS OF CONTROL, DAN PEMBERIAN REWARD TERHADAP BUDGETARY SLACK - Desmayani, Ni Made Mila Rosa; Suardhika, I Made Sadha (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
The purpose of this study was to determine the effect of participatory budgeting , locus of control and reward to the budgetary slack . Methods of data collection in this study using a questionnaire technique. This study population throughout the five-star hotel in the city of Denpasar. The sample used is purposive sampling method, using 3,4,5 star hotel in the city of Denpasar as many as 12 hotels. Number of samples 84, with the spread on 12 hotels in Denpasar. Research was conducted on 3,4,5 star hotel in the city of Denpasar. Data analysis technique used multiple linear regression. Based on test results, test results of the research instruments and the classical assumption test shows that all variables declared reliable and valid and meet the assumptions of classical test. Hypothesis testing results indicate that participatory budgeting, locus of control, and reward positive influence on budgetary slack.
Keywords: Participatory Budgeting; Locus Of Control; Giving Reward